Evaluation of restoration of an asbestos mine, in northern Greece, eight years after restoration works - Petros Ganatsas; Marianthi Tsakaldimi; Lazaros Ioannidis; Theologia Strafkou (Brawijaya University, 2021)
This paper deals with the evaluation of rehabilitation of spoils depositions of asbestos mine MABE, Kozani, in northern Greece, eight years after restoration works. In order to succeed this, we monitored all the restoration actions during the period of restoration works, as well as during the post-restoration period of eight years after the end of restoration works. The evaluation showed that the mining area subjected to restoration is now characterized, eight years after restoration, by high land stabilization, satisfactory woody vegetation cover, low erosion risk, low concentration of asbestos fibres in the air and water, and furthermore it was aesthetically integrated in the surrounding landscape. Even though the great difficulties due to the huge pile of spoils depositions that had been created during mining, the selection of the specific restoration actions greatly contributed to the achievement of a sustainable post-mining environment. The suitable land transformation, and the satisfactory establishment of forest vegetation created a safe from asbestos fibres environment, and for a sustainable future land use of the previous mine area as forest, which in many cases is the most appropriate post-mining use for contaminated mining areas.